2006
DOI: 10.1111/j.1475-6773.2006.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Medical Effectiveness for the California Health Benefits Review Program

Abstract: An important aspect of the mandate assessments requested by the California legislature is a review of the scientific and medical literature on the medical effectiveness of the proposed health insurance benefit mandate. Although such a review bears many similarities to effectiveness reviews that might be undertaken for publication as research studies, several important differences arise from the requirements of the California legislation. Our reviews are intended to assist the legislators in deciding whether to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…At least two reviewers screened the title and abstract of each citation identified to determine eligibility for inclusion. Full‐text articles were obtained and reviewers reapplied the initial eligibility criteria (Luft et al 2006). …”
Section: Review Of Medical Effectiveness Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…At least two reviewers screened the title and abstract of each citation identified to determine eligibility for inclusion. Full‐text articles were obtained and reviewers reapplied the initial eligibility criteria (Luft et al 2006). …”
Section: Review Of Medical Effectiveness Literaturementioning
confidence: 99%
“…For those trials where outcomes were reported in natural units, weighted averages for each outcome measure were computed without confidence intervals. For outcomes where there was more than one trial, we estimated a weighted average percentage change, using the sample size for each trial and the estimated proportionate change expected in the experimental group (Luft et al 2006). …”
Section: Review Of Medical Effectiveness Literaturementioning
confidence: 99%
“…CHBRP analyzes the possible effects of the proposed mandates on outcomes stipulated by the legislation or, if none are specified, the outcomes identified by qualified content experts as most important to evaluating the mandate's effectiveness. These findings are summarized in both text and tables (Luft et al 2006).…”
Section: A Description Of Chbrp and Its Medical Effectiveness Methodsmentioning
confidence: 98%
“…Here we focus on the lessons we have learned over the past six years from conducting medical effectiveness reviews for CHBRP. Our article builds on a series of papers published in 2006 that discuss the establishment of the program, the development of its analytic methods, and the first and second years of its operation (Halpin et al 2006; Kominski et al 2006; Luft et al 2006; McMenamin, Halpin, and Ganiats 2006; Oliver and Singer 2006; Philip 2006 ) . Over the ensuing years, the number of reports issued by CHBRP has grown from twenty‐two to fifty‐nine.…”
mentioning
confidence: 99%
“…As the articles elsewhere in this issue demonstrate, the review of proposed health insurance mandates is a highly technocratic exercise (Halpin et al 2006; Kominski et al 2006; Luft et al 2006; McMenamin, Halpin, and Ganiats 2006). It is produced and debated within a small, specialized group of policy professionals occupying positions inside and outside of government, often referred to as an issue network or policy community (Heclo 1978; Walker 1981; Kingdon 1984; Whiteman 1987).…”
Section: The Political Nature Of Health Insurance Mandatesmentioning
confidence: 99%